ADAT AMPIKALE: Asuransi Ala Masyarakat Bugis di Kecamatan Pammana Kabupaten Wajo - Hadi Daeng Mapuna (Universitas Islam Negeri Alauddin Makassar, 2020)
The Ampikale custom is a custom adopted by the Bugis community in Pammana District, Wajo Regency. The custom concept of Ampikale is that a person sets aside part of his inheritance to be used as a preparation for the cost of living in old age, the cost of care in case of illness and services for those caring for him until he dies. The basic concept of Ampikale has some similarities with the basic concept of insurance, which is the purpose, setting aside some of the assets or money and having people who will receive services. Therefore it can be said that the custom of Ampikale is insurance in the style of the Bugis community, Pammana District, Wajo Regency. How is the relationship between the custom concept of Ampikale and the basic concept of insurance, will be discussed in this paper.